2012
DOI: 10.1097/sap.0b013e31823f3cd9
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Complications Associated With Acellular Dermal Matrix-Assisted Breast Reconstruction

Abstract: In the studies evaluated, ADM-assisted breast reconstructions exhibited a higher likelihood of seroma, infection, and reconstructive failure than prosthetic-based breast reconstructions using traditional musculofascial flaps. ADM is associated with a lower rate of capsular contracture. A careful risk/benefit analysis should be performed when choosing to use ADM in implant-based breast reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
167
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(203 citation statements)
references
References 36 publications
5
167
4
3
Order By: Relevance
“…Using this technique, postoperative pain appears to be reduced and recovery is faster. Results are promising, with a complication rate comparable, if not superior to published series of subpectoral implant reconstruction with lower pole ADM coverage [8][9][10][12][13][14] and good aesthetic outcomes. The limited number of complications observed, despite adopting a new technique, may be explained by our previous extensive experience with the use of ADMs.…”
Section: Discussionsupporting
confidence: 48%
“…Using this technique, postoperative pain appears to be reduced and recovery is faster. Results are promising, with a complication rate comparable, if not superior to published series of subpectoral implant reconstruction with lower pole ADM coverage [8][9][10][12][13][14] and good aesthetic outcomes. The limited number of complications observed, despite adopting a new technique, may be explained by our previous extensive experience with the use of ADMs.…”
Section: Discussionsupporting
confidence: 48%
“…Many feel that esthetic outcomes are improved without an increase in complications; however, some studies have shown that there are increased complications in reconstructions using ADM, including mastectomy skin flap necrosis, infections, and explantation of the implant. 29,35,[38][39][40] Although the use of ADM is not without risk, in cases where total submuscular coverage is not possible, ADM allows for an improved result in immediate breast reconstruction.…”
Section: Acellular Dermal Matrixmentioning
confidence: 99%
“…The technique of implant-based reconstruction was further refined in the early 2000s with the use of dermal matrix as an inferior sling in both single-stage and tissue expander-based reconstruction. 29 Over the last decade, methods have continued to improve, making implant-based reconstruction a safe, reliable, and esthetically pleasing approach to breast reconstruction.…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%
“…Aesthetic advantages of HADM-assisted techniques include better definition and control of the implant pocket, better infra-and lateral mammary fold definition, more natural ptosis and reduced rates of capsular contracture (107)(108)(109). Data from meta-analyses have revealed slightly higher rates of seroma, infection and flap necrosis for HADM-assisted reconstructions compared with traditional, non-HADM-assisted techniques (110,111), although pooling of early results from multiple surgeons' initial experiences with the product may have biased the results (112). More recent studies have demonstrated that with judicious patient selection and precise intraoperative technique (113,114), superior aesthetic results can be achieved with a safety profile that is comparable with or superior to (115) reported series of traditional, non-HADM-assisted approaches (116)(117)(118).…”
Section: What Is the Role Of Acellular Dermal Matrix In Implantmentioning
confidence: 99%